Civil Engineering Contributions to Defense Industry Infrastructure: A Systematic Literature Review with a Focus on PT Pindad - Andinie, Ayu; Apriyanto, I Nengah Putra; Sudiarso, Aries (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the contribution of civil engineering to defense industry infrastructure, focusing on PT Pindad as Indonesia’s leading defense manufacturer. The aim is to bridge the literature gap between civil engineering practices and the strategic requirements of defense facilities. A Systematic Literature Review (SLR) was conducted under the PRISMA framework using Scopus, Web of Science, IEEE Xplore, and Google Scholar, resulting in 92 selected articles (2015–2025). Thematic analysis revealed distribution across three themes: infrastructure 40 articles (43.5%), sustainability 30 articles (32.6%), and technology 22 articles (23.9%). Findings confirm infrastructure as the operational backbone, while sustainability and technology are increasingly significant. The implication emphasizes resilient, sustainable, and technology-driven facilities to strengthen Indonesia’s defense industry independence.